2018
DOI: 10.3390/technologies6040121
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Topology of DF Relayed Terrestrial Optical Wireless Links with Generalized Pointing Errors over Turbulence Channels

Abstract: This study investigated the outage performance of a terrestrial FSO communication system that uses mixed series and parallel decode-and-forward (DF) relay-assisted (i.e., cooperative diversity) configurations, taking into account the influence of both atmospheric turbulence and pointing error effects. Turbulence-induced optical signal fading is modeled by gamma-gamma or the negative exponential distribution for weak to strong and saturated turbulence conditions, respectively. Additionally, weak to strong non-z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…In this work, a DF FSO relay-assisted system is considered, in which the source transmits the information signal towards the receiver across H serial paths, and consequently, across the (H-1) DF relay nodes. All of the H paths have the same length, D, and each relay node, after receiving the signal, decodes it and retransmits it to the next relay, or to the final node, i.e., the receiver [15,38] of the FSO system. Furthermore, we consider an OOK with IM/DD scheme, and the received signal at the h-th hop, y h , is given as [15,35,38]:…”
Section: Channel Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…In this work, a DF FSO relay-assisted system is considered, in which the source transmits the information signal towards the receiver across H serial paths, and consequently, across the (H-1) DF relay nodes. All of the H paths have the same length, D, and each relay node, after receiving the signal, decodes it and retransmits it to the next relay, or to the final node, i.e., the receiver [15,38] of the FSO system. Furthermore, we consider an OOK with IM/DD scheme, and the received signal at the h-th hop, y h , is given as [15,35,38]:…”
Section: Channel Modelmentioning
confidence: 99%
“…Many statistical distribution models have been proposed for the description of the intensity fluctuations which arise from the scintillation effect. Each properly describes the scintillation effect caused by different turbulence strength, i.e., weak, moderate or strong, [12,[14][15][16][17]. More precisely, lognormal and gamma statistical distributions are useful for describing the scintillations caused by weak turbulence, while GG, Malaga (M) and I-K are commonly used for a range from weak to strong turbulence conditions; finally, K and NE are suitable for strong and saturated conditions, respectively, [11,12,14,[18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, NZB pointing errors had never been examined in TOW literature, just as no method had been proposed in order to enhance the TOW outage performance and availability. Only, very recently, authors demonstrated for the first time, in [39], that a diversity method-i.e., in space, in time, or in wavelength-is an effective technique to enhance the outage performance of a typical TOW in terms of outage probability metric, by considering the joint impact of both attenuation-induced fading and misalignment-induced fading with NZB, modeled by the accurate Beckmann distribution [3,[41][42][43][44][45][46]. In basic terms, diversity refers to the consideration of multiple copies of the propagated signals in an attempt to overcome a poor transmission media state so as to reinforce the communication link's availability and robustness.…”
Section: Introductionmentioning
confidence: 99%